Delays in Breast Cancer Presentation and Diagnosis at Two Rural Cancer Referral Centers in Rwanda. (1st June 2015) - Pace, Lydia E.; Mpunga, Tharcisse; Hategekimana, Vedaste; Dusengimana, Jean‐Marie Vianney; Habineza, Hamissy; Bigirimana, Jean Bosco; Mutumbira, Cadet; Mpanumusingo, Egide; Ngiruwera, Jean Paul; Tapela, Neo; Amoroso, Cheryl; Shulman, Lawrence N.; et al.
Abstract : Background: Breast cancer incidence is increasing in low‐ and middle‐income countries (LMICs). Mortality/incidence ratios in LMICs are higher than in high‐income countries, likely at least in part because of delayed diagnoses leading to advanced‐stage presentations. In the present study, we investigated the magnitude, impact of, and risk factors for, patient and system delays in breast cancer diagnosis in Rwanda. Materials and Methods: We interviewed patients with breast complaints at two rural Rwandan hospitals providing cancer care and reviewed their medical records to determine the diagnosis, diagnosis date, and breast cancer stage. Results: A total of 144 patients were included in our analysis. Median total delay was 15 months, and median patient and system delays were both 5 months. In multivariate analyses, patient and system delays of ≥6 months were significantly associated with more advanced‐stage disease. Adjusting for other social, demographic, and clinical characteristics, a low level of education and seeing a traditional healer first were significantly associated with a longer patient delay. Having made ≥5 health facility visits before the diagnosis was significantly associated with a longer system delay. However, being from the same district as one of the two hospitals was associated with a decreased likelihood of system delay. Conclusion: Patients with breast cancer in Rwanda experience long patient and system delays before diagnosis; these delays increase the likelihood of more advanced‐stage presentations. Educating communities and healthcare providers about breast cancer and facilitating expedited referrals could potentially reduce delays and hence mortality from breast cancer in Rwanda and similar settings. Implications for Practice: Breast cancer rates are increasing in low‐ and middle‐income countries, and case fatality rates are high, in part because of delayed diagnosis and treatment. This study examined the delays experienced by patients with breast cancer at two rural Rwandan cancer facilities. Both patient delays (the interval between symptom development and the patient's first presentation to a healthcare provider) and system delays (the interval between the first presentation and diagnosis) were long. The total delays were the longest reported in published studies. Longer delays were associated with more advanced‐stage disease. These findings suggest that an opportunity exists to reduce breast cancer mortality in Rwanda by addressing barriers in the community and healthcare system to promote earlier detection. Abstract : Breast cancer rates are increasing in low‐ and middle‐income countries, with high case fatality rates, in part because of delayed diagnosis and treatment. The delays experienced by patients with breast cancer at two rural Rwandan cancer facilities were investigated. Longer delays were associated with more advanced‐stage disease. An opportunity exists to reduce breast cancer mortality in Rwanda by addressing barriers in the community and healthcare system to promote earlier detection.